ANALISIS FITOKIMIA DAN UJI TOTAL KAPANG PADA RUMPUT LAUT KERING Eucheuma denticulatum DAN Kappaphycus alvarezii - Mayore, Sutardy; Damongilala, Lena Jeane; Mewengkang, Hanny Welly; Salindeho, Netty; Sanger, Grace; Makapedua, Daisy Monica (Sam Ratulangi University, 2018)
The purpose of this study was to determine the phytochemistry content of dried seaweed Eucheuma denticulatum and Kappaphycus alvarezii using methanol and ethanol as solvents and to measure the total plate count (TPC) in the simplicia of dried seaweed Eucheuma denticulatum and Kappaphycus alvarezii. The results showed that dried seaweed Eucheuma denticulatum and Kappahycus alvarezii extract with ethanol and methanol contained bioactive compounds such as Flavonoids, Saponins, Tannins, Terpenoids, Phenols and Alkaloid in Dragendorf reagents and Wagner reagents. However, alkaloid was not found in Mayer reagents in both seaweed. Moreover, steroid was only identified in both seaweed extracts with ethanol. While total plate count (TPC) in incubation for two days at 25–30˚C was 3.1x102 CFU/g for dried seaweed Eucheuma denticulatum and Kappaphycus alvarezii had total plate count (TPC) of 3.4x102 CFU/g.Tujuan dari penelitian ini ialah untuk mengetahui kandungan fitokimia dari rumput laut kering Eucheuma denticulatum dan Kappaphycus alvarezii menggunakan pelarut methanol dan etanol, dan untuk mengukur total kapang dalam simplisia rumput laut kering Eucheuma denticulatum dan Kappaphycus alvarezii. Hasilnya menunjukkan bahwa rumput laut kering Eucheuma denticulatum dan Kappaphycus alvarezii yang di ekstrak dengan etanol dan methanol, mengandung senyawa Flavonoid, Saponin, Terpenoid, Tanin, Fenol dan Alkaloid pada pereaksi Dragendorf dan Wagner. Senyawa Alkaloid pada pereaksi Mayer tidak teridentifikasi pada kedua rumput laut. Senyawa Steroid yang teridentifikasi pada kedua rumput laut yang diekstrak dengan etanol. Sementara itu, total kapang yang di inkubasi selama dua hari pada suhu 25–30˚C ialah 3,1x102 CFU/g untuk rumput laut kering Eucheuma denticulatum, sedangkan rumput laut kering Kappaphycus alvarezii memiliki total kapang 3,4x102 CFU/g.